Strategi Aktor Incumbent Dalam Mempertahankan Jabatan Kepala Desa (Studi Kasus: Pemilihan Kepala Desa Serentak, Desa Pitra, Kecamatan Penebel Di Kabupaten Tabanan Tahun 2019) - Prasta Bisana, Gusti Agung; Ali Azhar, Muhammad; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2021)
This study aims to find out how the strategy of the incumbent actor in maintaining the position of village head in the simultaneous village head election in Pitra village, Penebel sub-district, Tabanan district in 2019. This research is framed with the Rational Choice theory from Barbara Geddes to see the rational choice of the actor who started it. with preferences which are then realized using the three basic frameworks of rational choice from Barbara Geddes and assisted by the presence of a local cultural component, namely the Stakeholder profession. Creating a loyal political machine and also streamlining the entire work program. The research method used is a descriptive qualitative research method using primary data and secondary data, because this study describes the strategy of incumbent actors in maintaining the position of village head in simultaneous village head elections in Pitra village, Penebel district, Tabanan district in 2019. Keywords: Actor Strategy, Village Head, Incumbent, Rational Choice, Simultaneous Pilkades 2019